464 Implantation of contemporary transcatheter aortic valves in small aortic annuli: the international multicentre TAVI-SMALL 2 registry. (8th December 2021) - Leone, Pier Pasquale; Regazzoli, Damiano; Cannata, Francesco; Pagnesi, Matteo; Chiarito, Mauro; Barbanti, Marco; Teles, Rui; Adamo, Marianna; Miura, Mizuki; Taramasso, Maurizio; Stefanini, Giulio; Mangieri, Antonio; et al.
Abstract: Aims: In patients with severe aortic stenosis, trans-prosthetic haemodynamics after transcatheter aortic valve implantation (TAVI) tend to be more favourable than after surgical aortic valve replacement, especially after self-expandable valve (SEV) implantation. The relative performance of TAVI according to leaflet position, that is supra-annular and intra-annular valves (SAV and IAV, respectively), has not been investigated thoroughly. Moreover, prosthesis-patient mismatch (PPM) is more common in patients with small aortic annuli, even though its clinical impact after TAVI is debated. Compare haemodynamics and clinical outcomes of transcatheter SAV and IAV in patients with small annuli. Methods: TAVI SMALL 2 is an international retrospective registry of 1378 patients with severe aortic stenosis and small annuli (annular perimeter <72 mm or area <400 mm 2 on computed tomography) treated with transfemoral transcatheter SEV (Evolut R/Pro, n = 750, Acurate Neo, n = 170 and Portico n = 172) and balloon-expandable valves (BEV, Sapien 3, n = 286) in 16 high-volume centres. Analyses were performed according to mechanism of valve release, that is SEV ( n = 1092) vs. BEV ( n = 286), and according to leaflet position, that is SAV (Evolut R/Pro and Acurate Neo, n = 920) vs. IAV (Sapien 3 and Portico, n = 458). Primary endpoints were pre-discharge mean aortic gradient and incidence of severe PPM. Secondary endpoint was incidence of all-cause mortality. Results: Pre-discharge mean aortic gradient was lower both after SAV vs. IAV (7.8 ± 3.9 vs. 12.0 ± 5.1, P <0.001) and SEV vs. BEV implantation (8.0 ± 4.1 vs. 13.6 ± 4.7, P <0.001). IAV implantation was more often complicated by severe PPM when compared to SAV implantation (8.8% vs. 3.6%, P = 0.007), and severe PPM was more common after BEV than after SEV implantation (8.7% vs. 4.6%, P = 0.041). At a median follow-up of 377 days (interquartile range 168–700 days), all-cause mortality occurred in 11.9% of patients after IAV and 9.4% after SAV implantation ( P = 0.172), and in 12.3% and 9.8% of BEV and SEV groups, respectively ( P = 0.218). Results were confirmed at Kaplan-Meier analysis (log-rank P = 0.748 and 0.687 for SAV vs. IAV and SEV vs. BEV, respectively, Figure 1). Pre-discharge more than mild paravalvular leak (PVL) was more common with SEV than BEV (11.6% vs. 2.6%, P <0.001), while incidence of more than moderate PVL was higher both after SAV vs. IAV (1.5% vs. 0.2%, P = 0.043) and SEV vs. BEV implantation (1.4% vs. 0%, P = 0.052). New permanent pacemaker implantation was higher after SEV than BEV (13.5% vs. 8.1%, P = 0.013). Conclusions: In this high-numerosity registry of patients with small aortic annuli, TAVI with SAV and SEV yielded a more favourable forward haemodynamic profile than after IAV and BEV implantation, respectively. All-cause mortality did not differ between groups.